Jurisprudencia del Consejo de Estado frente a la responsabilidad administrativa del Estado- Policía Nacional de Colombia en relación con los hechos personales del policía (2011-2016) - Diaz Correa, Nohelia Elizabeth (Archivos de criminología, seguridad privada y criminalística, 2021)
The study of the jurisprudence of the Council of State is approached regarding the administrative responsibility of the State-National Police of Colombia, in relation to personal facts of the policemen, for which a jurisprudential study of the decisions of the Council of State was carried out, identifying various titles of imputation of responsibility of the State for the acts of the police. At the same time, the "supervision and control" function that the police institution must carry out through the "commanders" was analyzed in front of the personnel, in order to minimize the possibility of convictions against the Colombian State for non-compliance with these functions. their uniforms and their reach. Finally, some recommendations were made regarding the exercise of supervision and control of human talent in the National Police